Perdre la mesure … Or, The Ecologics of Extinction. Issue 1 (April 2016) - Herbrechter, Stefan
Abstract : The article takes its cue from Olivier Rey's recent book Une question de taille (a question of size) and develops the idea of humanity 'losing its measure, or scale' in the context of contemporary ecological catastrophe. It seems true that the current level of global threats, from climate change to asteroids, has produced a culture of ambient 'species angst' living in more or less constant fear about the survival of the 'human race', biodiversity, the planet, the solar system. This indeed means that the idea of a cosmos and a cosmology may no longer be an adequate 'measurement' for scaling the so far inconceivable, namely a thoroughly postanthropocentric world picture. The question of scale is thus shown to be connected to the necessity of developing a new sense of proportion, an eco-logic that would do justice to both, things human and nonhuman. Through a reading of the recent science fiction film Interstellar, this article aims to illustrate the dilemma and the resulting stalemate between two contemporary 'alternatives' that inform the film: does humanity's future lie in self-abandoning or in self-surpassing, in investing in conservation or in exoplanets? The article puts forward a critique of both of these 'ecologics' and instead shows how they depend on a dubious attempt by humans to 'argue themselves out of the picture', while leaving their anthropocentric premises more or less intact.